Assessment of Environment in Selected Primary Schools in Mymensingh Municipality (Bangladesh Medical Journal, 2014)
A school health service is an economical and powerful means of raising community health Healthful school environment is one of the aspects of school health services. A descriptive, cross-sectional study was conducted at five purposively selected government and non-government primary schools in Mymensingh Municipality with a view to assess their environment. It was revealed that one (20.0%) school was situated in busy or crowded places, and one (20.0%) school did not have any enclosure. As many as 2 (40.0%) schools were located in low land. Most (4, 80.00%) of the schools were two-storied or multi-storied. One school did not have any facility for drinking water. Majority (3, 60.0%) of the schools were devoid of play-ground. It was observed that out of thirty-six, 17 (47.22%) classrooms were provided with non-attached and mixed type of seats and desks. At least 5 (15. 99%) class- rooms did not have cross-ventilation. The distance of blackboard was less than 7 feet from the front desks in 30 (80. 33%) class-rooms, while it was over 25 feet from the rear desks in 35 (97.22%) class-rooms. It was revealed that a significant number (24, 66.67%) of class-rooms accommodated more than 40 students, while a considerable number (33, 91.67%) of class-rooms had floor space less than 480 square feet. Moreover; only 8 (22.22%) class-rooms had 10 square feet floor space per student. It can be concluded that existing school environment is not acceptable at all, and should be improved to help in promoting growth and development of our future generations. Further large scale study should be carried out for better understanding of actual scenario of school environment existing in our country. DOI: http://dx.doi.org/10.3329/bmj.v40i2.18503 Bangladesh Medical Journal 2011 Vol.40(2): 31-35